Country Of Origin Dan Brand Reputation Terhadap Keputusan Pembelian Produk Mobil Wuling Di Kabupaten Kolaka - Anita, Anita; Astaginy, Niar; Titing, Andry Stepahnie (University of Riau Kepulauan, 2025)
This study investigates the impact of country of origin and brand reputation on the purchasing decisions of Wuling cars in Kolaka Regency. A quantitative method was employed to collect data from 120 respondents using a Likert scale questionnaire. Validity was assessed by comparing the calculated r with the table r, while reliability was measured using the Cronbach's Alpha method. The data were analyzed through Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results reveal that country of origin and brand reputation have a positive and significant influence on the purchasing decisions of Wuling cars in Kolaka Regency.